2003
DOI: 10.1093/jjco/hyg035
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Levels of Matrix Metalloproteinase-9 in Portal and Peripheral Blood is Useful for Predicting Liver Metastasis of Colorectal Cancer

Abstract: The results suggest that synchronous determination of the levels of MMP-9 in portal and peripheral blood would be useful for selecting colorectal cancer patients at high risk of hepatic recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…In human colorectal adenocarcinomas, the MMP-9 mRNA and the MMP-9 plasma protein levels are also increased compared with normal individuals (12,13). Interestingly, increased MMP-9 protein level measured in portal blood versus that measured in the peripheral blood has been reported to predict liver metastasis (14). By histologic localization studies, we and others have found previously that MMP-9 mRNA and/or protein are induced in a small subpopulation of macrophages located at the invasive front in the vicinity of the invasive cancer cells, suggesting that the MMP-9-expressing macrophages are important for the invasion of cancer cells into the normal tissues (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…In human colorectal adenocarcinomas, the MMP-9 mRNA and the MMP-9 plasma protein levels are also increased compared with normal individuals (12,13). Interestingly, increased MMP-9 protein level measured in portal blood versus that measured in the peripheral blood has been reported to predict liver metastasis (14). By histologic localization studies, we and others have found previously that MMP-9 mRNA and/or protein are induced in a small subpopulation of macrophages located at the invasive front in the vicinity of the invasive cancer cells, suggesting that the MMP-9-expressing macrophages are important for the invasion of cancer cells into the normal tissues (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…In cancer immunology, a clear role of MMP7 and of other MMPs has been shown in tumour growth and invasion (17,(20)(21)(22)(23)(24)(25). Increased MMP7 expression in tumour tissue, serum, lymph nodes and peritoneal liquid generally correlates with worse prognosis, a tendency for metastatic disease and reduced overall survival (18,(26)(27)(28)(29)(30)(31)(32). This suggests a possible role for MMP7 in the determination of locally advanced cancer in resected specimens, and in staging and planning for eventual adjuvant therapy, attesting to a potential role of MMP7 as prognostic factor and tumour marker (33) The effect of RT on MMP7 gene in human rectal cancer was first investigated in vivo by Kumar et al, who observed overexpression of MMP7 in radiated rectal cancer tissue compared to nearby irradiated normal rectal tissue (9).…”
Section: Discussionmentioning
confidence: 99%
“…MMPs participate in other processes infl uencing the primary tumour growth, angiogenesis and invasion, intra-and extravasation of metastatical cells and growth of metastatic process (19). The synchronous determination of the levels of MMP-9 in portal and peripheral blood is useful for selecting colorectal cancer patients at high risk of hepatic recurrence (20). TIMP-1 and -2 and MMP-2 were detected during tissue regeneration in rats while MMP-3, -9, -10, -13 and -14 were not (21).…”
Section: Discussionmentioning
confidence: 99%